Pembelajaran Pendidikan Agama Islam Berbasis Pengalaman: Urgensi dan Implementasi - Mokh. Imron Rosyadi (Faculty of Education and Teacher Training, Institut Agama Islam Negeri Pekalongan, 2017)
This present study starts from the basic question of the meaning, essence, and existence of Islamic education in experiencing global phenomena and the complexity of national issues that should be responded appropriately. Experience-based education has been deemed to be one of alternatives in developing teaching and learning processes that combine the basic concept of education with the primary essence of human beings. This essence denotes the teaching and learning process that presents various facts of life and regards humans’ skills to improve. This study used phenomenological approach to describe the concept of experience-based education that came to the surface from the education pattern of humanism demonstrated by the Western pragmatism. The deductive method was employed to explain definitions specifically, whereas the inductive one was applied to understand the process based on the particular data, and the presented data were concluded in general. The research findings reveal that experience-based education refers to the teaching and learning process that is actively carried out by providing dialogical relationship patterns. In these patterns, teachers play a pivotal role as a facilitator to explore and enhance their students’ potential by designing experience-based learning that is able to stimulate them to think and act. It is implemented by constructing experience to promote the students based on the integration of science and Islamic values. As a result, the teaching and learning process is always in line with the functions and objectives of education.